Aplikasi Inseminasi Buatan pada Induk Sapi Potong Menggunakan Se-men Cair Sapi Peranakan Ongole dengan Pengencer Cauda Epidydymal Plasma-2 + 0,6% Bovine Serum Albumin - Rachmawati, Achadiah; Ismaya, Ismaya; Widyobroto, Budi Prasetyo; Bintara, Sigit; Susilawati, Trinil (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
Artificial insemination (AI) in cattle using Ongole Cross Breed liquid semen with cauda epidydymal plasma-2 (CEP-2) diluent+0.6% Bovine Serum Albumin (BSA) aimed to improve the genetic quality of livestock with high sperm motility on beef cows. Addition of BSA as extracellular cryoprotectant to support egg yolk function to prevent membrane damage caused by cold shock during cold storage. This research was conducted in Tumpang, Pakis, and Singosari Sub-district, Malang Regency using 38 cows that inseminated using frozen semen of Limousine and Simmental breeds as control (19 cows) and liquid semen with CEP-2 + 0.6% BSA as a treatment (19 cows). The reproductive parameters were Non Return Rate (NRR), Service per Conception (S/C) and Conception Rate (CR). Data were analyzed descriptively and continued by chi-square test. The results showed that insemination using frozen and liquid semen did not affect the success rate of AI in beef cows. The NRR43-63 value of frozen was 89.40% and liquid semen was 78.94%; the CR value of frozen semen was 84.21% and liquid semen was 57.89%; and the S/C value of frozen semen was 1.21 and liquid semen was 1.42. The conclusions of the study were the values of NRR43-63, CR and S/C of frozen higher than liquidsemen.